ANALISIS BUTIR SOAL SECARA MODERN DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Muhamad Abdul Azis; Mudzakir Chabib (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Item analysis plays a pivotal role in modern educational evaluation, ensuring test items are valid and  reliable  in  measuring  student  competencies.  This  paper  delves  into  the  methodologies, applications,  and  benefits  of  modern  item  analysis,  leveraging  advanced  technologies  like  Item Response Theory (IRT), computerized adaptive testing (CAT), and big data analytics. It discusses essential  aspects  such  as  difficulty  index,  discrimination  index,  and  distractor  effectiveness, supported by expert opinions and software applications. Additionally, it highlights the challenges in adopting modern  analysis  methods,  such  as  access  to  technology,  user  expertise,  and  data management  issues.  The  paper  concludes  that  integrating  modern  item  analysis  significantly improves the quality of educational assessments.